Analisis perbandingan laporan keuangan dalam penerapan strategi business refocusing di Bank Muamalat pada tahun 2022 dengan 2023 - Ariiqoh, Sella Haniifatul (Maliki Interdisciplinary Journal, 2024)
This study analyzes a comparison of Bank Muamalat's financial statements for 2022 and 2023, focusing on the impact of implementing the business refocusing strategy. The main objective of this study is to evaluate the changes in the bank's financial performance after the implementation of the strategy. The method used is comparative analysis which includes ratio analysis. The results showed that Bank Muamalat's financial performance decreased in 2023. Strategies of operational efficiency, debt reduction, equity increase and risk management should be considered to improve future performance.